2016
DOI: 10.1111/1475-6773.12499
|View full text |Cite
|
Sign up to set email alerts
|

Resilience among Employed Physicians and Mid‐Level Practitioners in Upstate New York

Abstract: Objective. To investigate the factors associated with resilience among medical professionals. Data Sources/Study Setting. Administrative information from a rural health care network (1 academic medical center, 6 hospitals, 31 clinics, and 20 school health centers) was triangulated with self-report data from 308 respondents (response rate = 65.1 percent) to a 9/2013-1/2014 survey among practitioners serving a nine-county 5,600-square-mile area. Study Design. A cross-sectional questionnaire survey comprising val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 104 publications
(138 reference statements)
3
27
0
1
Order By: Relevance
“…Similar influences of personality were confirmed in Waddimba et al's [24] study of New York physicians and Cooke et al's [20] study of Australian general practitioners (GPs).…”
Section: Personality Traits and Resiliencesupporting
confidence: 56%
See 3 more Smart Citations
“…Similar influences of personality were confirmed in Waddimba et al's [24] study of New York physicians and Cooke et al's [20] study of Australian general practitioners (GPs).…”
Section: Personality Traits and Resiliencesupporting
confidence: 56%
“…The study by Bird et al [21] into resilience in American internal medicine residents was not able to analyse demographic associations with resilience due to a poor response to demographic questions. Eight of the other nine studies found that demographic variables (such as age, gender or marital status) had no influence on resilience scores [19][20]22,[24][25][26][27][28]. One study, by Eley et al [23] of rural general practitioners in Australia found that the oldest group of doctors (aged 52-61 years) had higher resilience levels (p=0.01).…”
Section: Demographic Influencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Waddimba és mtsai vizsgálatukban úgy találták, hogy a nagyobb rezilienciával jellemezhető orvosok bizonytalanságtűrése magasabb, elégedettebbek a munkájukkal és kollegiális támogatásukkal. Jelen vizsgálatunk eredményeihez hasonlóan, a demográfiai faktoroknak és a munkakörnyezet jellemzőinek nem volt kimutatható hatása a reziliencia alakulására [39].…”
Section: A Reziliencia Alakulása a Vizsgált Mintábanunclassified